(untitled) (World Bulletin of Social Sciences, 2026)
This article highlights the progress of reforms in the healthcare sector in recent years in our country, particularly in the Surkhandarya region. It examines the changes in the material and technical base of medical institutions in the region and the transition of the regional healthcare system to a new model.